Nanoplasmonic laser fusion response to Földes and Pokol. (6th December 2020) - Csernai, L. P.; Kroó, N.; Papp, I.; Strottman, D. D.
Abstract: Földes and Pokol in their letter "Inertial fusion without compression does not work either with or without nanoplasmonics" criticized our works. Here, we refute their argumentation. Our proposed improvement is the combination of two basic research discoveries: (i) the possibility of detonations on space-time hypersurfaces with time-like normal (i.e., simultaneous detonation in a whole volume) and (ii) to increase the ignition volume to the whole target, by regulating the laser light absorption using nanoantennas. These principles can be realized in an in-line, one-dimensional configuration, in the simplest way with two opposing laser beams as in particle colliders.